The Uyghur Problem in China’s Foreign Policy - Abdullayeva, Ulkar (Scholarya Demo Journal of Ruby, 2018)
The article is devoted to the study of the influence of the Uyghur problem on the internal and foreign policy of China.The study examines the history of advent and spread of Islam in China, attitudes towards Muslims, religious policy of People’s Republic of China (PRC), state of Muslim ethnic groups, Uyghur problem and its causes, and the reflection of this problem in China’s foreign policy. The chronology of events of the above-mentioned issues was considered in the study.The article discusses the linguistic, economic, social, religious and political causes of the Uyghur issue and examines the role of foreign forces in the aggravation of the problem, China’s use of this problem in the regulation of relations with its foreign competitors and ensurance of its international reputation. Moreover, it analyzes the reflection of the counter-terrorist ideas of the Western world in China’s foreign policy as well as the causes of controversial approaches of the USA to Uygur organizations such as the East Turkestan Islamic Movement and the Uygur World Congress that played a special role in the Uyghur movement. The study reviews different views and approaches of international relations experts and summarizes the results on the basis of comparative analysis.